POLA KOMUNIKASI DAKWAH IKATAN MAHASISWA MUHAMMADIYAH (IMM) DI MEDIA SOSIAL - Suriyati, Suriyati; Suriati, Suriati; Nur, Makmur Jaya; Syargawir, Syargawir; Ramadhan, Fauzan (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2025)
This study discusses the da'wah communication approach implemented by the Muhammadiyah Student Association (IMM) through the use of social media as a means of spreading Islamic messages. Applying a descriptive qualitative method, information was obtained through interviews with three key figures of IMM Sinjai Branch. The study results show that IMM actively produces da'wah content in the form of religious quotes, educational videos, and Islamic writings that are tailored to current digital media trends and the preferences of the younger generation. Social media platforms like Instagram, TikTok, and YouTube have become the primary choices due to their ability to reach audiences visually and interactively. The main challenges faced include the lack of enthusiasm among cadres towards da'wah content and the limited technical skills in content design. However, IMM demonstrates dedication through the organization of training, enhancement of digital literacy, and openness to public input to improve the quality of its preaching. This research emphasizes the need for a creative, contextual, and adaptive approach to preaching in response to the development of information technology to effectively target the younger generation